2013
DOI: 10.1371/journal.pone.0059041
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Structure of the Grasshopper Eyprepocnemis plorans in the South and East of the Iberian Peninsula

Abstract: The grasshopper Eyprepocnemis plorans subsp. plorans harbors a very widespread polymorphism for supernumerary (B) chromosomes which appear to have arisen recently. These chromosomes behave as genomic parasites because they are harmful for the individuals carrying them and show meiotic drive in the initial stages of population invasion. The rapid increase in B chromosome frequency at intrapopulation level is thus granted by meiotic drive, but its spread among populations most likely depends on interpopulation g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
(61 reference statements)
3
13
0
Order By: Relevance
“…But migratory species are often deemed to have less phylogeographic structure in their distribution range, as strong gene flow effects the homogenization of genetic variation as well as counteracts random drift, selection and mutation [63]–[66]. Higherφwithin populations than among populations suggests higher level of gene flow, in the light of the high dispersal ability reported for C. kiangsu , high levels of gene flow among populations and orderless phylogeographic relationship are perhaps convincing [67]. However, it has been shown that on large spatial scales, the ability of migration may not fully counteract the effect of geographical isolation.…”
Section: Discussionmentioning
confidence: 99%
“…But migratory species are often deemed to have less phylogeographic structure in their distribution range, as strong gene flow effects the homogenization of genetic variation as well as counteracts random drift, selection and mutation [63]–[66]. Higherφwithin populations than among populations suggests higher level of gene flow, in the light of the high dispersal ability reported for C. kiangsu , high levels of gene flow among populations and orderless phylogeographic relationship are perhaps convincing [67]. However, it has been shown that on large spatial scales, the ability of migration may not fully counteract the effect of geographical isolation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a study on grasshopper population genetic structure by Manrique‐Poyato et al . () who found that structure analysis based on data from loci with allelic dropout rates higher than 30% gave very similar results for both ∆K and the assignment of individuals to populations, as a second structure analysis on a reduced data set including only markers with low or no allelic dropout, suggesting that allelic dropout has a negligible effect on this type of analysis.…”
Section: Discussionmentioning
confidence: 89%
“…Studies using microsatellites have been mainly focused on their use as polymorphic markers in population genetics, genetic diversity, or kinship contexts (reviewed in Schlötterer and Pemberton 1998;Goldstein and Schlötterer 1999). This is particularly true in insects, where reports based on SSR molecular variation are abundant (Insuan et al 2007;Agustinos et al 2011;Blondin et al 2013;Manrique-Poyato et al 2013). In recent years, microsatellite genomic analysis has been powered by the development of high throughput next generation sequencing (NGS) technologies, based on massive sequencing approaches which enable a rapid, low-cost, and low time-consuming way to characterize microsatellites (Malausa et al 2011;Iquebal et al 2013).…”
Section: Introductionmentioning
confidence: 99%